Controlling the flight on double-handed foiling catamarans: The role of shared equipment on the crew members' mutual modes of regulation. (July 2022) - Terrien, Eric; Huet, Benoît; Saury, Jacques
Abstract: The purpose of this study was to contribute to the understanding of the role of shared sport equipment in the collective coordination of a team. It was conducted within an enactive approach of human cognition by mobilizing the methodological tools and methods of the Course of Action framework. Six crew members of hydrofoil sailing catamarans participated in this study. Data collection consisted in video-recording training sessions followed by individual self-confrontation interviews. A qualitative analysis of the data allowed typical modes of regulation of the flight to be characterized from each crew member's perspective. Three main modes of regulation were identified. All of them involved either salient perception of the boat's movements, or actions directed to regulating the boat's movement. In the discussion, we propose a distinction between three types of collective sport situations, regarding the role of the material environment of athletes in their coordination. This distinction opens new perspectives both for future research on team coordination, and for pedagogical and training implications. Highlights: Shared sport equipment plays an active role in the process of collective coordination. In the sailing of double-handed foiling catamarans, the boat can be considered as a "third partner". Research on team coordination should take into consideration different levels of implication of the material environment.